Effect of olefin block copolymer on the toughness of microcellular polypropylene composite. (1st March 2022) - Mao, Huajie; Li, Hao; Guo, Wei; Wu, Min; Zeng, Fankun
Abstract: Microcellular polypropylene (PP) materials have wide applications in the automotive industry and other fields due to their low density, high heat resistance, and environmental friendliness. To improve the toughness of foamed PP materials, the olefin block copolymer (OBC) toughened foamed PP materials, PP-G-MAH as compatibilizer, were prepared by foaming injection molding (FIM) to study the influence of OBC elastomer on the toughness of foamed PP composites. The crystallization behavior showed that the addition of OBC could increase the crystallinity and reduce the spherulite size of PP0, which benefited the improvement of toughness. The rheological measurement demonstrated that the melt viscosity of various PP0/OBC samples was significantly improved in contrast to those of PP0, which was good for the formation of the cell. The microstructure images showed that the cell sizes of the core layer and transition layer in the vertical section reached respectively 40.4 μ m and 27.3 μ m, as the content of OBC was 20 wt%. When 20 wt% OBC was added, the impact toughness of PP composites increased by 2.3 times, and the plastic deformation of the cell wall in the impact profile increased maximum, which could absorb a lot of energy and benefit for toughening. The representative volume element (RVE) model of PP/OBC foamed materials was established to simulate its impact and tensile process, taking into account the effect of elastomers and cells. The simulation results showed that the stress concentration factor of foamed PP under impact load increased from 1.80 to 1.93 by adding 20 wt% OBC content and 15 vol% void fraction, while the stress concentration factor of foamed PP under tensile load increased from 1.6 to 2.07 by adding 15 wt% OBC content and 15 vol% void fraction. The impact toughness of foamed PP composites with 20 wt% OBC and the tensile toughness of that with 15 wt% OBC reached the maximum with a 14.2% void fraction.